Impact of the Overloading of Heavy Goods Vehicles on the Fatigue Life of Steel Bridges - Ayilara, A.Q. (American Society of Civil Engineers (ASCE), 2017)
This paper presents the results of an investigation into the impact of overloading of trucks on fatigue life of member details of an existing highway steel bridge. Different traffic scenarios were investigated by varying the percentage of overloading and number of overloaded heavy goods vehicles in the total truck traffic population using 2 axle, 3 axle and 4 axle trucks. The nominal stress approach was used for global fatigue damage assessment of member details of a bridge. The results show that heavy goods vehicles should not be overloaded beyond 20 of their maximum allowable GVW and the number of overloaded trucks within the traffic population should not exceed 10. Overloading beyond this limits, increases the rate of fatigue damage to steel details by at least 20 and more. It was observed that a linear relationship exists between increase in GVW of heavy goods vehicles and fatigue damage to bridge details. © 2017 ASCE.